1987
DOI: 10.1346/ccmn.1987.0350306
|View full text |Cite
|
Sign up to set email alerts
|

Structural Study of a Benzidine-Vermiculite Intercalate Having a High Tetrahedral-Iron Content by 57Fe Mössbauer Spectroscopy

Abstract: Abstract-57Fe Mrssbauer spectra obtained at room temperature and 78 K for natural Mg-saturated, Casaturated, and benzidinium-intercalated vermiculite having a high tetrahedral iron content are presented. For all samples the spectra were computer-fitted with five overlapping doublets, representing Fe in both tetrahedral and octahedral sites. One doublet has parameters consistent with the weathered ilmenite known to be present as inclusions. For the intercalated vermiculite, the 6 value of the doublet assigned t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 15 publications
2
10
0
Order By: Relevance
“…This vermiculite contains about 70% of its Fe in tetrahedral coordination as indicated by chemical analysis and Mtssbauer spectroscopy (Cardile and Slade 1987). Cardile and Slade (1987) satisfactorily fit the MSssbauer spectrum of this vermiculite using a model that included: one IVFe3+ doublet; one trans VIFe3+ doublet; one cis VIFe3+ doublet; and one doublet having IS = 0.6 mm/s and QS = 1.65 ram/s, attributed to ilmenite growths. A similar model was used in the present work (Table 3), and the two sets of Mtssbauer parameters are in good agreement for the 2-layer hydrate.…”
Section: Msssbauer Spectra Of Nontronite and Vermiculite Samples At Amentioning
confidence: 66%
See 2 more Smart Citations
“…This vermiculite contains about 70% of its Fe in tetrahedral coordination as indicated by chemical analysis and Mtssbauer spectroscopy (Cardile and Slade 1987). Cardile and Slade (1987) satisfactorily fit the MSssbauer spectrum of this vermiculite using a model that included: one IVFe3+ doublet; one trans VIFe3+ doublet; one cis VIFe3+ doublet; and one doublet having IS = 0.6 mm/s and QS = 1.65 ram/s, attributed to ilmenite growths. A similar model was used in the present work (Table 3), and the two sets of Mtssbauer parameters are in good agreement for the 2-layer hydrate.…”
Section: Msssbauer Spectra Of Nontronite and Vermiculite Samples At Amentioning
confidence: 66%
“…One way to test this is to demonstrate a similar effect to that observed in the M6ssbauer spectrum of SWa-1 by Luca and Cardile (1989) on samples which indisputably contain IVFe3 § The Koegas nontronite examined by Goodman et al (1976) and the Phalaborwa vermiculite examined by Cardile and Slade (1987) are good candidates because they have been shown by chemical analysis to contain about 16% Fe 3+ substitution in the tetrahedral sheet. This IVFe3 § content was corroborated by M6ss-bauer spectroscopy.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Several authors [9,29,30,46,47] also found that Palabora vermiculite has, comparatively, an unusually high level of iron. These iron ions (and also aluminium ions) are the main isomorphous substitutes for magnesium in the octahedral sites and also as considerable silica replacements in the tetrahedral sites [46].…”
Section: Resultsmentioning
confidence: 99%
“…These iron ions (and also aluminium ions) are the main isomorphous substitutes for magnesium in the octahedral sites and also as considerable silica replacements in the tetrahedral sites [46].…”
Section: Resultsmentioning
confidence: 99%